Bimetallic PdNi catalyst on cattail Leaves-Derived nanoporous carbon support for synthesis of partially hydrogenated fatty acid methyl ester (H-FAME) - Tripob Longprang; Napat Kaewtrakulchai; Worapon Kiatkittipong; Atthapon Srifa; Nuwong Chollacoop; Apiluck Eiad‐ua; Suttichai Assabumrungrat (Arabian Journal of Chemistry, 2024)
Cattail leaves (CL) have been used as a carbon source to synthesize nanoporous carbon (NPC) support with high surface area (SBET = 2002.12 m2g−1) via hydrothermal carbonization and potassium hydroxide (KOH) activation. The studied catalysts, including monometallic Pd/NPC and Ni/NPC, and bimetallic PdNi/NPC, were synthesized and characterized by using several techniques (e.g., scanning electron microscopy, transmission electron microscopy, nitrogen sorption, Fourier transform infrared spectroscopy, thermogravimetric analysis, and X-ray diffraction). Their catalytic activity toward partial hydrogenation of palm biodiesel to H-FAME was tested, and the liquid product composition, cloud point, and oxidation stability were determined. The studied catalysts have a high porosity with the SBET of approximately 2037.34–2187.96 m2g−1 led to excellent metal dispersion. Although Ni did not show high catalytic activity compared to Pd, Ni incorporated with Pd as PdNi/NPC catalyst significantly increased the cis-C18:1 selectivity and prevented the catalytic deactivation during the partial hydrogenation. The oxidation stability of palm biodiesel feedstock was increased from 13.69 to 17.12 h while the cloud points adversely increased by only 3 degrees from 12 to 15 °C (still lower than 16 °C of the Thai industrial recommendation) with bimetallic PdNi/NPC catalyst. In conclusion, the main benefit of bimetallic PdNi/NPC over monometallic Pd/NPC and Ni/NPC is shown through not only higher C18:2 conversion but also much higher cis-to-trans ratio of C18:1 resulting in higher oxidation stability with acceptable compromise on the cloud point increasing. Consequently, the produced palm H-FAME can be used at a high blend ratio.
Keywords: Catalysis and Hydrodesulfurization Studies; Biodiesel Production and Applications; Catalysis for Biomass Conversion